Pilot study of safety and feasibility of DNA microseeding for treatment of spontaneous canine melanoma. Issue 3 (22nd May 2017) - Zuleger, Cindy L.; Kang, Chulhi; Ranheim, Erik A.; Kurzman, Ilene D.; Macklin, Michael D.; Newton, Michael A.; Wolchok, Jedd D.; Vail, David M.; Eriksson, Elof; Albertini, Mark R.
Abstract: Spontaneous canine malignant melanoma provides an excellent pre‐clinical model to study DNA vaccines for melanoma immunotherapy. A USDA‐approved xenogeneic human tyrosinase (huTYR) plasmid DNA vaccine delivered intramuscularly induces detectable immune responses and has clinical activity in some dogs with melanoma. The objective of this pilot study was to evaluate the feasibility, safety and immunogenicity of huTYR plasmid DNA administered to the skin via microseeding in dogs with spontaneous melanoma. DNA microseeding utilizes a modified tattooing device as an alternate and potentially more potent delivery method for DNA immunization. DNA was delivered to shaved inner thigh skin of six companion dogs with melanoma approximately every 14 days for a planned total of four vaccination time points. An anti‐huTYR ELISA was used to test pre‐ and post‐treatment sera. Biopsies of treated skin were obtained for detection of huTYR transgene expression. DNA microseeding was well tolerated with no significant toxicity detected beyond local site irritation, and there were no signs of autoimmunity. huTYR‐expressing cells were observed in biopsies of huTYR DNA microseeding sites. Increased humoral anti‐huTYR antibodies were seen in two of five evaluable dogs following microseeding compared to baseline. DNA microseeding is well tolerated in companion dogs with melanoma. Further investigation is needed to determine if combining DNA microseeding with other immunotherapy regimens potentiates this delivery platform for cancer immunotherapy. Abstract : This study is the first report of the clinical safety, transgene expression and immunogenicity of repeated DNA microseeding in an animal with a spontaneous tumour. We report that microseeding of xenoantigen DNA into dog skin is safe, well tolerated, and does not elicit local or systemic allergic reactions. Exploratory analyses of humoral responses against the xenoantigen, human tyrosinase, as well as expression of human tyrosinase in treated skin, are reported.